2019
DOI: 10.1002/ecy.2894
|View full text |Cite
|
Sign up to set email alerts
|

Trees of Amazonian Ecuador: a taxonomically verified species list with data on abundance and distribution

Abstract: We compiled a data set for all tree species collected to date in lowland Amazonian Ecuador in order to determine the number of tree species in the region. This data set has been extensively verified by taxonomists and is the most comprehensive attempt to evaluate the tree diversity in one of the richest species regions of the Amazon. We used four main sources of data: mounted specimens deposited in Ecuadorian herbaria only, specimen records of a large‐scale 1‐hectare‐plot network (60 plots in total), data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 29 publications
4
19
0
Order By: Relevance
“…We are aware this might represent a limitation because taxonomic specialists not usually consider this material for species names confirmation. However, in the past 5–8 years the number of fertile material for many of our vouchers have been collected by the authors or other researchers and the taxonomy of the plot network verified (Guevara et al 2019 ). In many other cases our extensive experience in Amazonian tree species identification gives us confidence in the accuracy of the taxonomy in our plot network.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We are aware this might represent a limitation because taxonomic specialists not usually consider this material for species names confirmation. However, in the past 5–8 years the number of fertile material for many of our vouchers have been collected by the authors or other researchers and the taxonomy of the plot network verified (Guevara et al 2019 ). In many other cases our extensive experience in Amazonian tree species identification gives us confidence in the accuracy of the taxonomy in our plot network.…”
Section: Methodsmentioning
confidence: 99%
“…species in a single hectare (ter Steege et al 2013;Guevara et al 2019;ter Steege et al 2019;ter Steege et al 2020). Thus, describing and analysing the patterns of species and lineage composition across spatial and environmental gradients is fundamental to understand the mechanistic causes that promote community assembly of this hyper-diverse ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing deforestation and the scarcity of comprehensive botanical records pose significant challenges in the identification, monitoring, and effective conservation of forest species within the EAR. A study conducted by Guevara et al [ 38 ] suggests that about 71.8% of the tree species identified in the lowlands have fewer than five observations with no geographic duplicates. This lack of information is critical because conservation efforts become hindered without understanding a species’ geographic distribution patterns and biotic interactions within its habitat [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of this group, 2766 species have been assessed as being in the category of least concern, 992 are considered vulnerable, 769 are endangered, and 275 are critically endangered [ 47 ]. On the other hand, a previous study by Guevara et al [ 38 ], with a database of 47,486 individuals collected from lowland trees in the EAR, identified 106 species as currently classified as Least Concern, 78 as Vulnerable, 16 as Endangered, 9 as Data Deficient, and 1 as Critically Endangered. On the other hand, the same study found that 89% of lowland tree species in the EAR are currently listed as Not Evaluated.…”
Section: Introductionmentioning
confidence: 99%